Exposure to ambient air pollutions and its association with adverse birth outcomes: a systematic review and meta-analysis of epidemiological studies - Desye, Belay; Berihun, Gete; Geto, Abebe Kassa; Berhanu, Leykun; Daba, Chala (Frontiers in Public Health, 2024)
IntroductionAir pollution is a significant global public health concern. However, there is a lack of updated and comprehensive evidence regarding the association between exposure to ambient air pollution and adverse birth outcomes (preterm birth, low birth weight, and stillbirth). Furthermore, the existing evidence is highly inconsistent. Therefore, this study aims to estimate the overall association between ambient air pollution and adverse birth outcomes.MethodsIn this study, initially a total of 79,356 articles were identified. Finally, a total of 49 articles were included. We conducted compressive literature searches using various databases, including PubMed, Scientific Direct, HINARI, and Google Scholar. Data extraction was performed using Microsoft Excel, and the data were exported to STATA 17 software for analysis. We used the Joanna Briggs Institute’s quality appraisal tool to ensure the quality of the included studies. A random effects model was employed to estimate the pooled prevalence. Publication bias was assessed using funnel plots and Egger’s regression test.ResultsIn this study, the pooled prevalence of at least one adverse birth outcome was 7.69% (95% CI: 6.70–8.69), with high heterogeneity (I2 = 100%, p-value < 0.001). In this meta-analysis, high pooled prevalence was found in preterm birth (6.36%), followed by low birth weights (5.07%) and stillbirth (0.61%). Exposure to PM2.5 (≤10 μg/m3) throughout the entire pregnancy, PM2.5 (≤10 μg/m3) in the first trimester, PM10 (>10 μg/m3) during the entire pregnancy, and O3 (≤10 μg/m3) during the entire pregnancy increased the risk of preterm birth by 4% (OR = 1.04, 95% CI: 1.03–1.05), 5% (OR = 1.05, 95% CI: 1.01–1.09), 49% (OR = 1.49, 95% CI: 1.41–1.56), and 5% (OR = 1.05, 95% CI: 1.04–1.07), respectively. For low birth weight, exposure to PM2.5 (≤10 μg/m3) and PM2.5 (>10 μg/m3) throughout the entire pregnancy was associated with an increased risk of 13% (OR = 1.13, 95% CI: 1.05–1.21) and 28% (OR = 1.28, 95% CI: 1.23–1.33), respectively.ConclusionThis study highlighted a significant association between ambient air pollution and adverse birth outcomes. Therefore, it is crucial to implement a compressive public health intervention.Systematic review registrationThe review protocol was registered with the record ID of CRD42024578630.